The means by which writers present a proposition as an opinion in English research articles - Loi, Chek Kim; S. Akkakoson; Henry Bating; Norazah Mohd Suki; Chow T. Soon; Nur Shafiekah Sapan (IJLLL, 2019)
The present study is a part of an ongoing research. It is both qualitative and quantitative and it aims to contribute to an understanding of how hedging devices and strategies are exploited throughout the sampled English research articles. The corpus of the present study is made up of the discussion sections of English research articles published between 2013 and 2017. Twenty English research article discussions restricted to empirical studies were randomly selected from the Journal of English for Academic Purposes. The statistical data measures (i) the percentage of total research article discussions employing the four hedging orientations and (ii) the percentage of total research article discussions employing hedging items in specific categories. Each hedging orientation is contributed by the linguistic items/taxonomy of hedges by Hyland (1996)